First record of Baylisascaris procyonis in the wild invasive Northern raccoon (Procyon lotor) in the Czech Republic - Benovics, Michal; Švantnerová, Lívia; Mikulka, Ondřej; Škorpíková, Lucie; Skoták, Vlastimil; Cukor, Jan (Frontiers in Veterinary Science, 2025)
Baylisascaris procyonis, a zoonotic nematode originated in North America, is a significant cause of larva migrans in humans and wildlife. Here we report the first confirmed record of B. procyonis in free-ranging invasive Northern raccoons (Procyon lotor) in the Czech Republic, based on combined morphological and molecular evidence. 10 raccoons were examined from the Doupov Highlands subpopulation between 2023 and 2025, B. procyonis were recovered from three individuals. Morphological and molecular analyses of ITS and COI regions confirmed the species identity, showing 99.3%−100% similarity to known conspecific sequences. This finding extends the recognized range of this zoonotic parasite in Central Europe, underscoring the potential public health risks posed by environmental contamination with infective eggs. Our results highlight the need for ongoing surveillance of invasive raccoon populations to monitor the spread of this pathogenic zoonotic parasites.